2000
DOI: 10.1002/1096-8652(200009)65:1<25::aid-ajh4>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal vaccine administration associated with splenectomy: The need for improved education, documentation, and the use of a practical checklist

Abstract: An audit was performed of the documentation of pneumococcal vaccination in splenectomy patients in three major hospitals involving a geographical population base of 350,000 patients in British Columbia, Canada. Overall, 111 of the 164 hospitalized splenectomy patients (68%) had received pneumococcal vaccination. Of elective splenectomy cases, only 11 of 55 (20%) had been vaccinated prior to surgery, as is currently recommended. One hundred fifty-five patients (95%) had splenectomy status mentioned in the disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…The need for future revaccination or possibility of future post-splenectomy sepsis was not mentioned in discharge summaries or medical files for any patient. In another similar study conducted in Canada, the need for future revaccination was mentioned for 6% of the patients, and the possibility of post-splenectomy sepsis was mentioned only for 5% of the patients, which is similar to ours results (18). These results are considered to be unsatisfactory and show that we need to improve administrative procedures.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The need for future revaccination or possibility of future post-splenectomy sepsis was not mentioned in discharge summaries or medical files for any patient. In another similar study conducted in Canada, the need for future revaccination was mentioned for 6% of the patients, and the possibility of post-splenectomy sepsis was mentioned only for 5% of the patients, which is similar to ours results (18). These results are considered to be unsatisfactory and show that we need to improve administrative procedures.…”
Section: Discussionsupporting
confidence: 87%
“…The recommendation for patients is to receive a written information about the post-splenectomy risks, medical alert bracelet and up-to-date vaccination card (11,17). In addition, it is necessary to start using splenectomy registers, because then we will be able to follow up all splenectomized patients and increase the adherence to vaccination (18). Splenectomy status was mentioned in discharge summaries for all forty-seven patients (100%), while vaccination status was mentioned for 40 patients (85,1%), which is similar to other reports (18).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Brigden et al 14 reported that only 68% of patients in their survey received pneumococcal vaccination. A similar vaccination rate was observed in a Danish study by Ejstrud et al, 15 with the lowest rate of vaccination occurring in patients splenectomised during radical cancer surgery or for iatrogenic trauma.…”
Section: Discussionmentioning
confidence: 97%
“…It displays a slowly progressive course [20]. About 7% of CF patients will develop clinically obvious portal hypertension [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. How many evolve to hepatic function failure is still not well established, but from practice, it seems rare [1].…”
Section: Discussionmentioning
confidence: 99%